THE DEVELOPMENT OF STUDENTS’ WORKSHEET USING SCIENTIFIC APPROACH ON CURRICULUM MATERIALS - M. Khairi Ikhsan; Handayani. SB Handayani. SB (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Scientific approach is a learning approach that is designed to make learners work actively in constructing concepts and principles through the stages observed (to identify or find the problem), to formulate the problem, propose or formulate hypotheses, collect data with a variety of techniques, analyzing the data, draw conclusions and communicate the concept. To support the implementation of the learning with scientific approach, scientific learning tools such as student’s worksheet is required. Students’ worksheet, as one of learning tools that is used to involve the students to work actively during teaching and learning process, should be developed based on the students’ need. Students’ worksheet with scientific approach in teaching curriculum has not developed well yet. A good student’s worksheet must be satisfied criteria of valid, practical and effective. This research is a developmental research using 4-D, without the dissemination phase. It has been conducted on 32 students of STKIP PGRI Sumbar academic year 2012. In this study, data obtained from Curriculum syllabus analysis, students’ need analysis and results of validation. Students’ need analysis was done to analyze the students’ perception about the previous learning materials and to know what kind of learning material they need. From the results and discussion on this research, it was found that the students’ had bad perception about the previous Curriculum learning material in score 58.07. It was also found that the development of student’s worksheet satisfies aspect of validity (average total validity is 75,4). Therefore developed student’s worksheet in the category of was good.